Understanding significant experiences of adolescent athletes’ participation in competitive sports life: a systematic review - Dongoran, M. Fadli; Setyawati, Heny; Kristiyanto, Agus; Raharjo, Hermawan Pamot; Setiawan, Caly (Frontiers in Sports and Active Living, 2025)
This research aims to investigate the significant experiences of adolescent athletes in competitive sports activities and their development through the available literature. This study systematically reviews research on adolescent athletes participating in competitive sports over the past 10 years. We evaluated and reported 19 studies in four sections: sample characteristics, research design, significant experiences, and key findings related to the development of adolescent athletes. This study includes adolescent athletes who participate in various sports and pursue careers in organized and competitive sports using qualitative and mixed methods designs. This study employs a systematic literature review as its research method. The initial online search was conducted in April 2023 and updated on January 2025 on electronic databases: Web of Science (WoS), PubMed, and Scopus. The process of searching for articles used the PRISMA guidelines proposed by Moher. We synthesized and interpreted the findings in each article. The main findings of this study lead to three main themes: meaningful experiences for adolescents, barriers in the development of adolescent athletes, and that influencing athlete development. This study concludes that working with adolescent athletes requires attention to unseen factors to ensure that they are in a supportive environment that encourages their positive development into elite athletes in the future.